Keputusan Pembelian Konsumen Berdasarkan Citra Merek, Cita Rasa dan Harga Produk Supermi di Kota Yogyakarta - Astuti, Defria Dwi; Gusti, Yenni Kurnia (Universitas Batanghari, 2024)
This research looks at how brand image, taste, and price influence consumers' decisions to buy Supermi. The authors conducted this study to discover and analyze whether brand image, taste, and price have an impact on consumer purchasing decisions. The population of Yogyakarta City who have consumed Supermi brand instant noodles. A sample of 100 respondents was selected using the Roscoe formula. The sampling method is simple random sampling and uses the Likert scale to measure research data collected through questionnaires. SPSS 25.0 is used for testing. Test results show that taste and price have a partial impact on purchasing decisions, while decisions about what to buy are not influenced by brand image. Brand taste, price, and taste, simultaneously impact consumers' decisions to buy Supermi products.